2019
DOI: 10.3390/s19030553
|View full text |Cite
|
Sign up to set email alerts
|

Deploying Acoustic Detection Algorithms on Low-Cost, Open-Source Acoustic Sensors for Environmental Monitoring

Abstract: Conservation researchers require low-cost access to acoustic monitoring technology. However, affordable tools are often constrained to short-term studies due to high energy consumption and limited storage. To enable long-term monitoring, energy and space efficiency must be improved on such tools. This paper describes the development and deployment of three acoustic detection algorithms that reduce the power and storage requirements of acoustic monitoring on affordable, open-source hardware. The algorithms aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…This may entail processing data in a distributed fashion using small, inexpensive system-on-chip processing devices coupled to the recording device, or the use of purpose-made recording devices with software for onboard processing, e.g. AudioMoth (Hill et al 2017, Prince et al 2019. Such distributed processing nodes could communicate potential detections to biologists remotely over mobile data networks, streamlining the process of retrieving data from the field and allowing for very rapid responses to emergent issues at field sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This may entail processing data in a distributed fashion using small, inexpensive system-on-chip processing devices coupled to the recording device, or the use of purpose-made recording devices with software for onboard processing, e.g. AudioMoth (Hill et al 2017, Prince et al 2019. Such distributed processing nodes could communicate potential detections to biologists remotely over mobile data networks, streamlining the process of retrieving data from the field and allowing for very rapid responses to emergent issues at field sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, any sensor type related to the context of our application, such as microphones and vision cameras, have advantages and disadvantages [13,14]. Multispectral imaging has been suggested in a different context to our work in agriculture and entomology [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Research on those sounds has revealed that it is possible to obtain reliable information of a taxonomic classification and this could be used to measure the biodiversity of a habitat as presented in [5]. The development of tools to have knowledge of the biodiversity will give more information and indicators about the state of the biodiversity [6]. In particular, insects play an important role in ecological balance and biodiversity conservation [4,7].…”
Section: Introductionmentioning
confidence: 99%